Analisis Pengaruh Tingkat Suku Bunga Terhadap Dana Nasabah di Bank Syariah - Muzan, Amrul; Rahman, Rifqy; Permata Sari, Tina; Farhat, Muhammad Farhat (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2024)
This research aims to analyze the influence of interest rates on customer funds in Islamic banks and identify strategies that can be implemented by Islamic banks to maintain and increase customer trust and loyalty. This research uses a qualitative approach, by collecting data through in-depth interviews with customers and managers of Islamic banks as well as analysis of related literature. The research results show that changes in conventional interest rates can influence customers' decisions in depositing or withdrawing their funds at Islamic banks. To overcome this, Islamic banks need to develop investment portfolio diversification strategies, including products that provide protection against inflation such as real assets. In addition, Islamic banks must improve transparency, staff professionalism and customer service quality. Education and effective communication regarding the benefits and advantages of sharia products are also important to build customer trust and loyalty. The practical implications of this research include developing competitive products, increasing the use of digital technology for customer service, and regularly evaluating and adjusting strategies to respond to market changes. By implementing these measures, Islamic banks can increase their competitiveness, maintain customer loyalty, and achieve sustainable growth.